Analysis of syntactic complexity in Elementary School aged 7-8 years - Saputri, Vira Amandita; Husadani, Rizki; Sudrajad, Kiyat (Mitra PGMI: Jurnal Kependidikan MI, 2025)
This research aims to identify the profile of syntactic complexity abilities in elementary school aged 7 - 8 years in Surakarta. This research uses a quantitative approach with a survey-based descriptive design using multi-stage sampling which focuses on observing a single variable. Each respondent's sentence complexity will be calculated using analysis of language samples obtained from the results of the conversation, and the results will be analyzed descriptively statistically. The results show that interrogative, complex and compound-complex sentences are in the low group. Complete sentences, subject, predicate, object, information, declarative, simple, compound, active and passive are in the medium group. The syntactic abilities of children aged 7-8 years are mostly adequate, but have not yet reached their maximum potential. The role of teachers, speech therapists, and parents is important in optimizing this development through active language stimulation, syntactic structure practice, and early detection, taking into account environmental and social factors.